The effect of foliar feeding with nutrients (N, K, B) and gibberellic acid in improving vitality of pollen, and reducing the drop of set fruits of "Meyer" lemon trees - داؤد, جوى; جرجس مخول; فهد صهيوني (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out in (Bahloulia) a sub-district of Latakia governorate during the 2022 agricultural season on 15-year-old lemon trees (Mayer) which planted at 4*4m distance . The purpose of this paper is to examine the effect of foliar feeding with nutrients (N,k,B) and Gibberellic acid GA3 on improving flowering and reducing fruit drop rates. Based on the important role played by foliar spraying with nutrients to enhance flower setting and perserve fruits by reducing fruit drop rates. The study included 11 treatments in which foliar sprays were used with four chemical compounds: urea, potassium sulfate, boron and gibberellic acid, individually and in combination, at different concentrations (2.5 g/L, 1.5 g/L, 200ppm, 20ppm), respectively, in addition to the untreated control. The results showed that the spraying treatment with the four compounds combined (GA3, N, B, K) was superior to all studied treatments in terms of pollen vitality and amounted to (98.1%), followed by the spraying treatment (boron + k2so4) and (boron + urea) with a percentage of (97%) compared to the control sample (71.1) The results showed the superiority of spraying treatment with the four compounds combined (GA3, N, B, K) in terms of germination rate (74.24%), followed by spraying treatment (boron + (GA3) and (urea + boron) with a percentage of (72.30%) and (72.23%), respectively, compared to the control sample (50.79%). And The results also showed the spraying treatment with the four compounds combined (GA3, N, B, K) outperformed all studied treatments in terms of flowers setting rates and amounted to (14.01%), followed by the spraying treatment (Boron + Urea) with a rate of (10.73%), and then the Boron spraying treatment. And Gibberellic acid (10.09%). Compared with the control sample, in which the setting percentage did not exceed (1.30%). The results also showed the superiority of the foliar spray treatment with the four compounds combined (GA3, N, B, K) over all the studied treatments in terms of reducing the drop rate by (85.98%), followed by the two foliar spray treatments (B, GA3) and (GA3, N). ) with a rate of (89.91%) and (89.25%) compared to the control sample (98.70%). Therefore, based on this study, it is recommended to use foliar feeding with elements (N, B, K) and gibberellic acid to improve the set percentage, increase pollen vitality, and reduce the percentage of fruit drop after set.